2017
DOI: 10.1038/s41598-017-13170-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a positive Sea Surface Temperature anomaly on a Mediterranean tornadic supercell

Abstract: Extreme events represent a topic of paramount importance and a challenge for modelling investigations. Due to the need of high-resolution models, the study of severe localized convective phenomena is even more critical, especially in relation to changes in forcing factors, such as sea surface temperatures (SSTs), in future climate scenarios. Here, we analyze the effect of changes in SSTs on the intensity of a tornadic supercell in the Mediterranean through modelling investigations. We show dramatic (nonlinear)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…From a local influence perspective, clearer connections were obtained with respect to SST anomalies in the Bay of Biscay. In particular, the SST anomalies reveal their role as a significant factor of natural climate variability, modulating thermodynamic instability, and hence convective activity (Molina et al, 2016;Piazza et al, 2016;Wills et al, 2016;Miglietta et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a local influence perspective, clearer connections were obtained with respect to SST anomalies in the Bay of Biscay. In particular, the SST anomalies reveal their role as a significant factor of natural climate variability, modulating thermodynamic instability, and hence convective activity (Molina et al, 2016;Piazza et al, 2016;Wills et al, 2016;Miglietta et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the NHTPs, we also analysed upstream anomalies of SST representing a significant contribution to the natural variability of the climate system which can locally modulate the atmospheric circulation, particularly in terms of moisture availability (e.g. Piazza et al, 2016;Miglietta et al, 2017). In our study, we used the NOAA Optimum Interpolation (OI) SST V2, which is interpolated from direct and indirect measurements on a global grid with a spatial resolution of 1 • × 1 • (Reynolds et al, 2002).…”
Section: Sea-surface Temperaturementioning
confidence: 99%
“…Over Europe, there has been recent examination on the variations in thunderstorm frequency induced by the North Atlantic Oscillation (NAO) and sea surface temperatures in the Mediterranean or the North Atlantic Ocean (e.g. Miglietta et al, ; Piper & Kunz, ). The NAO was found to have a significant impact on lightning probability with its negative (positive) phases generally favoring (reducing) convective activity (e.g.…”
Section: Climate Interactionsmentioning
confidence: 99%
“…The simulations showed that, together with the mesoscale environment, the convection triggered by the Sila mountain (Calabria region) was favourable to the development of the tornadic supercell. The positive sea surface temperature anomaly was also found to strongly affect the intensity of the supercell (Miglietta et al, ).…”
Section: Previous Studiesmentioning
confidence: 99%